Selection of anti-cytokine biologics by pretreatment levels of serum leucine-rich alpha-2 glycoprotein in patients with inflammatory bowel disease - Takahiro Amano; Takeo Yoshihara; Shinichiro Shinzaki; Yuko Sakakibara; Takuya Yamada; Naoto Osugi; Satoshi Hiyama; Yoko Murayama; Koji Nagaike; Hideharu Ogiyama; Toshio Yamaguchi; Yuki Arimoto; et al. (Scientific Reports)
Abstract Serum leucine-rich alpha-2 glycoprotein (LRG) can monitor disease activities during biologics treatment in patients with inflammatory bowel disease (IBD). It is unclear whether the pretreatment serum LRG level can predict clinical effectiveness including serum trough levels of ustekinumab in patients with IBD. This multicenter prospective cohort study included 184 patients (Crohn’s disease, 104; ulcerative colitis, 80) who received ustekinumab (n = 119) or anti-tumor necrosis factor (n = 65) between January 2019 and March 2023. Multivariate logistic regression analysis revealed serum LRG level at week 0 (0w-LRG, odds ratio 0.12, 95% confidence interval 0.02–0.68) as one of significant factors for clinical remission at week 8. We divided patients into the low- and the high-LRG groups by the median 0w-LRG (18.2 µg/mL) and compared the effectiveness. In patients who received ustekinumab, the proportion of clinical remission at week 8 was significantly different between in the low- (76.9%) and in the high-LRG group (59.3%, P = 0.038), and median serum trough level at week 8 was significantly different between in the low- (10.9 µg/mL, interquartile range 6.7–13.4) and the high-LRG group (5.3 µg/mL, interquartile range 2.4–8.3, P < 0.001). The 0w-LRG can predict the effectiveness including serum trough levels of ustekinumab during induction treatment for patients with IBD.